1999
DOI: 10.1007/s002619900547
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of a pancreatic pseudocyst into the portal venous system

Abstract: Pseudocyst formation is a well-known complication of acute or chronic pancreatitis. We report a case in which pseudocyst ruptured into the splenic and portal veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…1,2 In particular, pancreatitis is known to cause portal vein thrombosis. 1 Yamamoto et al 15 reported occlusion of the portal vein due to rupture of a pancreatitisassociated pancreatic pseudocyst into the portal vein. 15 In our case, prior to the development of pylethrombophlebitis, the patient had undergone pancreaticojejunostomy with internal anastomosis of the jejunum and a pancreatic cyst, which was close to the portal vein.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,2 In particular, pancreatitis is known to cause portal vein thrombosis. 1 Yamamoto et al 15 reported occlusion of the portal vein due to rupture of a pancreatitisassociated pancreatic pseudocyst into the portal vein. 15 In our case, prior to the development of pylethrombophlebitis, the patient had undergone pancreaticojejunostomy with internal anastomosis of the jejunum and a pancreatic cyst, which was close to the portal vein.…”
Section: Discussionmentioning
confidence: 98%
“…1 Yamamoto et al 15 reported occlusion of the portal vein due to rupture of a pancreatitisassociated pancreatic pseudocyst into the portal vein. 15 In our case, prior to the development of pylethrombophlebitis, the patient had undergone pancreaticojejunostomy with internal anastomosis of the jejunum and a pancreatic cyst, which was close to the portal vein. We assessed the lipase concentration in the drained fl uid and compared it with the serum lipase concentration; lipase activity was slightly higher in the drained fl uid than in the serum (150 vs. 69 U/l).…”
Section: Discussionmentioning
confidence: 98%
“…Development of this venous complication is distinctly unusual. In fact, only a few cases have been reported in the literature [96,97]. Diagnostic confirmation of the fistula cannot be achieved by angiography because the portal tree is excluded from the systemic circulation because of its cystic transformation.…”
Section: Diagnosis and Management Of Venous Complicationsmentioning
confidence: 96%
“…Emergent surgical exploration is usually required. While an internal drainage should always be aimed for, usually a thorough abdominal lavage and external drainage are all that can be achieved safely [43, 44]. …”
Section: Complicationsmentioning
confidence: 99%